Characterization of Phase Resolved Partial Discharge waveforms from instrument transformer using statistical signal processing technique - Thayoob Y.H.M.; Ahmed S.K.; Piau C.C.; Ping C.Y.; Balasubramaniam Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric instrument transformers; Electric transformer testing; Electric transformers; Electric waveforms; High frequency transformers; Image processing; Instrument testing; Partial discharges; Signal detection; Stochastic systems; High frequency current transformers; inteferences; Non-intrusive sensors; Partial discharge activity; Partial discharge detection; Phase resolved partial discharge patterns; Phase resolved partial discharges; Statistical signal processing; Signal processing